Formation of the Concept of “Administrative Act” in the European Administrative-Legal Doctrine - V. V. Maslov (Теоретическая и прикладная юриспруденция)
The article focuses on the formation of the main approaches to the content of the concept of an administrative act in European administrative law. The subject of the analysis is either the rule of law or the doctrine of France, Germany, Italy and Spain. The author notes that administrative act as an independent category arises in France as a result of the creation of a separate administrative jurisdiction. The article gives a detailed analysis of the evolution of approaches to the administrative act in France, as a result, the author shows gradual narrowing of its content and reveals its prerequisites. The author states that the interpretation of the administrative act given by M. Hauriou as an expression of the will of the administration in order to cause legal consequences served as the basis for the application (with some adaptation) civil law developments regarding legal transactions (invalidity of administrative acts, conditional administrative acts, etc.) to administrative act. The article examines the approaches of the German doctrine and shows common features and differences between the concept of an administrative act in Germany and in France. The study determines construction of an administrative act by analogy with a judicial decision as a characteristic feature of the German legal order. In this regard, its focus on the settlement of a specific case becomes its key parameter, which, unlike France, excluded the possibility of considering regulatory acts of the administration as a type of administrative acts. Much attention is given to the approaches to the administrative act in Italy and Spain. The author shows that these countries point departed from the French and German traditions in the middle of XX century and adopted a much broader definition of the administrative act.